Faunal exploitation during the Proto-Zhou period in the Jing River Valley: Evidence from Sunjia and Xitou - Festa, Marcella; Dou, Haifeng; Monteith, Francesca; Orton, David; Wang, Qianwen; Zong, Tianyu; Liu, Bin; Li, Yue (Frontiers in Earth Science, 2023)
This study examines faunal assemblages from Proto-Zhou sites of Sunjia and Xitou, which are located in the Jing River Valley, in Central Shaanxi, to address questions concerning the exploitation of different animal resources in the context of the Shang-Zhou dynastic transition in the late eleventh century BCE. Through examining two small assemblages, this study demonstrates that the inclusion of such assemblages is essential to building upon our understanding of the human exploitation of animal resources. These zooarchaeological analyses showed an increase in husbandry, with pig farming being complemented by extensive caprine and cattle herding. A diversified use of animal resources, and especially the larger number of bovids, could have been prompted by the need for a wider and more efficient exploitation of the immediate environment, in response to growing climatic deterioration, in addition to an increase in interactions with northern pastoral communities. Our biometric analysis results also support the current regional narrative that diverse faunal use could reflect the development of socio-economic complexity in the Jing River Valley in the late second millennium BCE.